The Influence of Mind Mapping Type Cooperative Learning Methods towards the Learning Outcomes of Islamic Religious Education Students at SMAN 12 Makassar: Pengaruh Metode Pembelajaran Kooperatif Tipe Mind Mapping terhadap Hasil belajar Pendidikan Agama Islam Peserta Didik di SMAN 12 Kota Makassar - Khayrun, M; Lataf, Budiarto; Bahriani, Demitri; HN, Firmansyah; Fauzan, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2024)
This study aims to eval__uate the effect of the cooperative learning method of Mind Mapping on students' learning outcomes in Islamic Religious Education (PAI) at SMAN 12 Makassar. The research used a quasi-experimental method with a Nonequivalent Control Group Design involving two groups: the experimental group taught using the Mind Mapping method, and the control group taught using conventional methods. Each group consists of 35 students. Descriptive analysis results show that the average pretest score of the experimental group was 68.40, while the average post-test score significantly increased to 82.51. A normality test revealed that the data was normally distributed with an Asymp. Sig. (2-tailed) value of 0.200. Furthermore, the Paired Samples Test indicated a significant difference between pretest and post-test scores, with a mean difference of 14,114 points and a p-value of < 0.001, demonstrating that the Mind Mapping method had a significant effect on improving learning outcomes. The correlation test between pretest and post-test scores resulted in an r-value of 0.885, indicating a strong relationship between the two variables. Based on these findings, the cooperative learning method of Mind Mapping significantly impacts improving students' learning outcomes in Islamic Religious Education. This method is effective in helping students organize and comprehend the concepts being taught, leading to an overall improvement in academic performance. Therefore, the Mind Mapping method is an effective learning strategy for Islamic Religious Education at the high school level.